Avantgardni vektor oblikovanja: sestop historičnih avantgard v polje vsakdanjega življenja - Berk, Ksenija (Monitor ISH, 2006)
The paper analyses certain trends of historical avant-gardes and their entry into everyday life through the practice of design. In the era of postmodernism, they have re-emerged as an alternative to high modernism and legitimised a wide range of neo-avant-garde initiatives. Such avant-garde vectors in the field of design are exemplified by the manifesto First Things First 2000, which recycles the ideas of historical avant-gardes in the manner of a postmodernist collage, thus revealing the Utopian mentality of contemporary society. Rather than a successor of historical avant-gardes, the FTF 2000 manifesto is the logical result of art being transplanted to industrial production and neoliberal capitalism.
Keywords: historične avantgarde; oblikovanje; manifest; blagovna estetika